Getting started for internet of things with Launch Pad and ESP8266 - Singh, Rajesh; ProQuest (Firm) (Gistrup, Denmark : River Publishers, 2019)
Getting Started for Internet of Things with Launch Pad and ESP8266 provides a platform to get started with the Ti launch pad and IoT modules for Internet of Things applications. The book provides the basic knowledge of Ti launch Pad and ESP8266 based customized modules with their interfacing, along with the programming. The book discusses the application of Internet of Things in different areas. Several examples for rapid prototyping are included, this to make the readers understand the concept of IoT. The book comprises of twenty-seven chapters, which are divided into four sections and which focus on the design of various independent prototypes. Section-A gives a brief introduction to Ti launch pad (MSP430) and Internet of Things platforms like GPRS, NodeMCU and NuttyFi (ESP8266 customized board), and it shows steps to program these boards. Examples on how to interface these boards with display units, analog sensors, digital sensors and actuators are also included, this to make reader comfortable with the platforms. Section-B discusses the communication modes to relay the data like serial out, PWM and I2C. Section-C explores the IoT data loggers and shows certain steps to design and interact with the servers. Section-D includes few IoT based case studies in various fields. This book is based on the practical experience of the authors while undergoing projects with students and partners from various industries.
24.1.1.2 Circuit diagram for local server with NodeMCU 239 -- 24.1.1.3 Circuit Diagram for Local Server with GPRS 240 -- 24.1.2 Program Code 241 -- 24.1.3 Thing Speak Server 253 -- 24.2 Fire Detector and Emergency Hooter System in Building 254 -- 24.2.1 Circuit Diagram 255 -- 24.2.2 Program Code 257 -- 24.2.3 Blynk App 259 -- 25 Case Study on Internet of Thing-based Agriculture Field Monitoring 261 -- 25.1 Green House Monitoring System 261 -- 25.1.1 Circuit Diagram 264 -- 25.1.1.1 Circuit diagram for the sensor node 264 -- 25.1.1.2 Circuit diagram for local server 265 -- 25.1.2 Program Code 266 -- 25.1.3 Main Server 274 -- 25.2 Water Tank Monitoring and Control in Agriculture Field 274 -- 25.2.1 Circuit Diagram 276 -- 25.2.2 Program Code 277 -- 25.2.3 Blynk App 282 -- 26 Case Study on Internet of Things in Smart Home 285 -- 26.1 Electrical Appliances Control System 285 -- 26.1.1 Circuit Diagram 286 -- 26.1.2 Program Code 287 -- 26.1.3 Blynk App 293 -- 26.2 Electrical Appliances Dimming Control System 293 -- 26.2.1 Circuit Diagram 294 -- 26.2.2 Program Code 295 -- 26.2.3 Blynk App 300 -- 27 Case Study on Internet of Thing in Healthcare 303 -- 27.1 Heart Rate Monitoring System 303 -- 27.1.1 Circuit Diagram 304 -- 27.1.2 Program Code 305 -- 27.1.3 Blynk App 307 -- 27.2 ECG Monitoring System 308 -- 27.2.1 Circuit Diagram 309 -- 27.2.2 Program Code 310 -- 27.2.3 Blynk App 312 -- 27.3 Blood Pressure Monitoring System 312 -- 27.3.1 Circuit Diagram 313 -- 27.3.2 Program Code 314 -- 27.3.3 Blynk App 316 -- Bibliography 317 -- Index 319 -- About the Authors 321.
Includes bibliographical references and index.
Description based on print version record
Rajesh Singh, Anita Gehlot, Lovi Raj Gupta, Bhupendra Singh, Priyanka Tyagi
eBooks on EBSCOhost
Keywords: Internet of things; Internet des objets; COMPUTERS / Programming Languages / General; COMPUTERS / Networking / General; Internet of things